Drought assessment in the island region of Iraq - Majid, Ahmad; Mohammad Ali, Yousif (Al-Adab Journal, 2020)
The research marked (Drought Assessment in the Al-Jazeera Region in Iraq) focused on studying and analyzing the reality of drought in the Al-Jazeera regions within the borders of Iraq only, and the research reached through a study of thermal Zones to the presence of a significant rise in temperature, especially during the last period of the study periods, as The fifth thermal Zone, which ranged between (23.1-24) C°, recorded an area ratio of (2, 10.7)% during the third and fourth periods, respectively, which means rise temperatures at the end of the study period, while the rainy Zones were completely the opposite of temperature, where it was recorded Rain decreased significantly, so the rainy zones recorded the same (more than 400 mm) ratio of an area of ​​(1, 4.1%) during the first and second disappeared periods this zones during the third and fourth periods. The changes in the thermal and rainy zones are reflected in the increased frequency of drought phenomenon in the Al-Jazeera region, as the effective rain factor recorded two types of climate varieties; The first is the arid climate, which was characterized by a significant increase in its impact area by an area of ​​(66.8, 64.8, 88, 83.5)% during the four study periods in a row, and the second classified the semi-arid climate with an area of ​​(33.2, 35.2, 12, 16.5)% Respectively and the decline in the area of ​​this variety was at the expense of the increase in the first category of climate, which is dry climate.